2021
DOI: 10.1111/mve.12546
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of fleas and their hosts in the trifinio of north‐east Argentina: first detection of Rickettsia asembonensis in Ctenocephalides felis felis in Argentina

Abstract: Fleas are important in public health due to their role as parasites and vectors of pathogens, including Rickettsia. The aim of this study was to evaluate the diversity, abundance and prevalence of fleas and the presence of Rickettsia in the trifinio of north-east Argentina. Fleas from household and synanthropic animals were obtained from urban and periurban areas. They were taxonomically identified and samples of 227 fleas in 86 pools were analysed by polymerase chain reaction targeting the gltA and ompB genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
1
0
3
Order By: Relevance
“…Rickettsia asembonensis is an emerging flea-borne agent, closely related to Rickettsia felis and other R. felis -like organisms, that belongs serologically to the spotted fever group of rickettsiae [SFGR] but genetically to the transitional group of rickettsiae [ 2 ]. R. asembonensis was first identified in Kenya in 2013, and since then, multiple studies have reported its global detection in a variety of arthropods collected from domestic, peri-domestic, and wildlife animals [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Although its pathogenicity and role as a human pathogen has not yet been elucidated, its detection in both human [ 10 , 11 , 12 , 13 ] and animal [ 14 , 15 , 16 ] specimens suggests a potential public health threat.…”
Section: Introductionmentioning
confidence: 99%
“…Rickettsia asembonensis is an emerging flea-borne agent, closely related to Rickettsia felis and other R. felis -like organisms, that belongs serologically to the spotted fever group of rickettsiae [SFGR] but genetically to the transitional group of rickettsiae [ 2 ]. R. asembonensis was first identified in Kenya in 2013, and since then, multiple studies have reported its global detection in a variety of arthropods collected from domestic, peri-domestic, and wildlife animals [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Although its pathogenicity and role as a human pathogen has not yet been elucidated, its detection in both human [ 10 , 11 , 12 , 13 ] and animal [ 14 , 15 , 16 ] specimens suggests a potential public health threat.…”
Section: Introductionmentioning
confidence: 99%
“…Algunos de los ectoparásitos aquí mencionados tienen importancia desde el punto de vista de la salud pública (p. ej. O. bacoti o A. triste) por lo cual resulta importante registrar su hallazgo en los distintos hospedadores, sobre todo considerando que estos pueden habitar en zonas urbanizadas y sobre todo teniendo en cuenta el patrón generalista de distribución que presentan (Lareschi, 2004;Nava et al, 2008Nava et al, , 2017Lareschi et al, 2007;Urdapilleta et al, 2020Urdapilleta et al, , 2021.…”
Section: Discussionunclassified
“…Comentarios: en el presente estudio solo se colectó una hembra. Se destaca la importancia sanitaria de esta especie en el ciclo del helminto zoonótico Dipylidium caninum y en el ciclo enzoótico de bacterias de los géneros Rickettsia y Bartonella (Horta et al, 2006;Brown & Macaluso 2016;Urdapilleta et al, 2020Urdapilleta et al, , 2021.…”
Section: Descripción Morfológica: (Figs 23 a B Y C)unclassified
See 1 more Smart Citation